(untitled) (Al-Qamar, 2022)
Jurisprudential sciences have a prominent and unique importance in Sharī‘ah knowledge. It refers to the rules with the help of which the Sharī‘ah rulings are deduced from their arguments and sources. Historically two schools of thought regarding the compilation of this branch of knowledge, the Hanafites school and the Mutakalimīn school are well prominent. The method of the Hanafites is called inductive and that of Mutkalimīn is called deductive. The Hanafite scholars have derived rules based upon the ’ijtihādāt of their a’immah and mujtahidīn while the followers of the second methodology compiled the rules by keeping the Sharī‘ah texts in front of them and then applied these rules for various jurisprudential derivations. These two approaches complied by the jurists have a centuries’ history of contention between them. Then a new method emerged that was a combination of these two. It was named the comprehensive method of jurisprudential legislation. A well reputed name among the founders of this method is Ṣadr-al- Sharī‘ah ‘Ubaydullāh ibn Mas‘ūd(d. 747 AH). He wrote a book on comprehensive principles of jurisprudence called al-Tanqīḥ, then to explain the same book, the author himself wrote a book called al-Tawḍīḥ. On this later book about forty-eight commentaries were written with the passage of time. In this article, the human being called Maḥkūm ‘alayh in Islamic Jurisprudence has been focused. Allāh Ta’ālāy, the one who commands are called ‘Ḥākim’ and the commandment is called ‘Maḥkūm Fīh’ and these two are the basic elements of Jurisprudence. The subjugated party is called the commanded person (Mukallif) in this article, various conditions of the ‘mukallif’ will be mentioned, the occasions on which the Sharī‘ah order is revoked from the ‘mukallif’. The thoughts of Ṣadr-al- Sharī‘ah will be specifically focused, what the eligibility disorder is, and its types are, will also be discussed, the commandment about such situations will be studied to unveil the aspect of ease in Sharī‘ah. The cosmopolitan concept of Islamic Jurisprudence will be presented by introducing comprehensive principles of jurisprudence based upon which a comprehensive Islamic Jurisprudence can be deduced which may introduce itself as Islamic Jurisprudence instead of Ḥanafī, Shāfa‘ī Mālikī or Ḥanbalī schools of Islamic Jurisprudence.